Performance evaluation of the Roche Elecsys® Anti-SARS-CoV-2 immunoassays by comparison with neutralizing antibodies and clinical assessment - Takei, Satomi; Ai, Tomohiko; Yamamoto, Takamasa; Igawa, Gene; Kanno, Takayuki; Tobiume, Minoru; Hiki, Makoto; Saito, Kaori; Khasawneh, Abdullah; Wakita, Mitsuru; Misawa, Shigeki; Miida, Takashi; et al. (PloS one, 2022)
Quantitative measurement of SARS-CoV-2 neutralizing antibodies is highly expected to evaluate immune status, vaccine response, and antiviral therapy. The Elecsys® Anti-SARS-CoV-2 S (Elecsys® anti-S) was developed to measure anti-SARS-CoV-2 S proteins. We sought to investigate whether Elecsys® anti-S can be used to predict neutralizing activities in patients’ serums using an authentic virus neutralization assay. One hundred forty-six serum samples were obtained from 59 patients with COVID-19 at multiple time points. Of the 59 patients, 44 cases were included in Group M (mild 23, moderate 21) and produced 84 samples (mild 35, moderate 49), while 15 cases were included in Group S (severe 11, critical 4) and produced 62 samples (severe 43, critical 19). The neutralization assay detected 73% positive cases, and Elecsys® anti-S and Elecsys® Anti-SARS-CoV-2 (Elecsys® anti-N) showed 72% and 66% positive cases, respectively. A linear correlation between the Elecsys® anti-S assay and the neutralization assay were highly correlated ( r = 0.7253, r 2 = 0.5261) than a linear correlation between the Elecsys® anti-N and neutralization assay ( r = 0.5824, r 2 = 0.3392). The levels of Elecsys® anti-S antibody and neutralizing activities were significantly higher in Group S than in Group M after 6 weeks from onset of symptoms ( p < 0.05). Conversely, the levels of Elecsys® anti-N were comparable in both groups. Three immunosuppressed patients, including cancer patients, showed low levels of anti-S and anti-N antibodies and neutralizing activities throughout the measurement period, indicating the need for careful follow-up. Our data indicate that Elecsys® anti-S can predict the neutralization antibodies in COVID-19.